Perbedaan Proporsi Jumlah Siswa Kelas XII SMA Al Islam 1 Surakarta yang Mengalami Depresi pada Kelompok dengan Kualitas Hidup dan Harga Diri Tinggi dan Rendah - Heryadi, Afrizal Tri; Yuliadi, Istar; Aisyah, Siti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Adolescents aged 10-20 years experienced a rapid change in the size, shape, physiological, psychological and social function. In normal development, a teenager has a tendency to get depressed. To overcome that, a teenager need self-esteem and quality of life. The purpose of this study is to determine the differences in the proportion of students number of 12th Class Al Islam 1 Senior High School Surakarta, experiencing depression on the group with high or low quality ofÂ life and self-esteem. Methods: This study is an observational study with cross sectional analytical conducted in July 2014 in Al Islam 1 Senior High School Surakarta. Sampling is conducted for the entire 12th class with purposive random sampling conducted for students with high self-esteem (25%) and low self-esteem (25%) and students with a high quality of life (25%) and a lower quality of life (25 %). Correspondent filling: (1)The contents of personal data; (2)L-MMPI questionnaire; (3)Rosenberg questionnaire to assess the self-esteem scores; (4)WHOQOL BREF questionnaire to assess quality of life scores; (5)BDI Questionnaire to assess depression scores. Data obtained for 96 students and the data were analyzed using Chi Square through 19.00 SPSS for Windows. Results: This study indicates: (1)Significant differences in the proportion of depression in a group of students with high and low self-esteem in Al Islam 1 Senior High School Surakarta (p<0.05) and the prevalence ratio of 0.4; (2)Significant difference in the proportion of depression in a group of students with high and low quality of life in Al Islam 1 Senior High School Surakarta (p<0.05) and the prevalence ratio of 0.3. Conclusions: (1)There is a significant difference in the proportion of depression in a group of students with high and low self-esteem and high and low quality of life in Al Islam 1 Senior High School Surakarta. Students with high self-esteem has the possibility to experience depression 0.4 times greater than students with low self-esteem and students with a high quality of life has the possibility to experience depression 0.3 times greater than students with lower quality of life. Keywords: Adolescence, quality of life, self-esteem, depression Â